Proximate Composition and Fatty Acid Profile of Namakkal Quail-1 - Karthika, S.; Sureshkumar, S.; Chandirasekaran , V.; Senthilkumar, R.P. (Journal of Meat Science, 2015)
The aim of this study was to evaluate the proximate composition and fatty acid profiles of Namakkal quail-1 meat. The birds were reared in cage system and they were fed with standard broiler starter mash up to 6 weeks of age. Twenty four birds were selected randomly (12 male and 12 female) at 4th and 6th week of age and they were slaughtered by the following standard method. From each carcass breast muscle samples were collected for the proximate and fatty acid analysis. Results showed that the moisture and gross energy had no significant (p>0.05) effect on age and sex of the birds. Crude protein and total ash had significant effect on both age and sex of the birds. Both were high at 4th week in male birds (23.38±0.53 and 1.56±0.08). The ether extract had significant effect only on age of the birds, which was high in 6th week birds (4.85±0.20). The fatty acid analysis showed that between age groups linolenic acid, palmitoleic acid, linoleic acid and DHA were differed significantly (p>0.05) while between sexes, linolenic acid, oleic acid and DHA showed significant (p>0.05) effect. Linoleic acid was high (27.30±0.03) in 4th week while DHA, linolenic acid and palmitoleic acid were high (1.20±0.08, 0.68±0.31 and 6.83±0.03) in 6th week birds. Between sexes, linoleic acid, linolenic acid, oleic acid and DHA (27.42±1.15, 1.30±0.11, 36.03±0.63 and 0.74±0.13) were high in female birds. The MUFA was high in 4th week birds while PUFA and omega-3 was high in 6th week birds. The MUFA and PUFA were high in male birds.